The Influence of attitude toward behavior, subjective norm, and perceived behavior control on entrepreneurial intentions with self confidence as a mediation variable - Paskalis Aditya Putra; Firman Firman (Marketing Management Studies, 2022)
The purpose of this study is to find out the influence of attitude toward behavior, subjective norm, perceivedbehavior control on entrepreneurial intentions with self-confidence as a mediation variable. The method that will be applied in this research is quantitative research methods. The population of this study of all students at the Faculty of Economics, Padang State University sampling is by purposive sampling. Sample number 100 students. The data will be collected through questionnaires distributed through a google form. Analytical methods are used descriptive and quantitative analysis through path analysis using SPSS 25.0.. The results showed that: (1) Attitude Toward Behavior has a positive effect on Entrepreneurial Intention (2) Subjective Norm has a significant positive effect on Entrepreneurial Intention (3) Perceived Behavior Control has a significant positive effect on Entrepreneurial Intention (4) Self Confidence does not mediate the influence of Attitude Toward Behavior on Entrepreneurial Intention (5) Self Confidence does not mediate norm subjective effect on Entrepreneurial Intentio (6) Self Confidence mediates the influence of Perceived Behavior Control on Entrepreneurial Intention.